1981
DOI: 10.1111/j.1744-313x.1981.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

INCOMPATIBILITY FOR OR PRE‐IMMUNIZATION AGAINST M1s DETERMINANTS DECREASES LETHAL GRAFT‐VERSUS‐HOST REACTION DEVELOPED ACROSS NON ‐ H ‐ 2 AND/OR H‐2 BARRIERS

Abstract: SUMMARY The effect of incompatibility for Mls determinants was studied in lethal graft‐versus‐host reaction (GVHR) in the mouse. GVHR was induced in adult recipients of the following H‐2k strains: (AKR x B10.BR)F1 (MlsB/Mlsb); (C3H x B10.BR)F1 (Mlsc/Mlsb); (CBA/J x B10.BR)F1 (Mlsd/Mlsb) and (CBA/H x B10.BR)F1 (Mlsb). Recipient mice were heavily irradiated and grafted with bone marrow and spleen cells from H‐2 compatible B10.BR (H‐2k, Mlsb) or H‐2 incompatible B10.D2 and B10 donors were normal, while those from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This conclusion corre-lates with observations suggesting that products of the Mls" locus have a regulatory role in the recognition of other DBA/2 antigens in vitro [20]. As suggested by several experiments [21,221, the suppressive effect of MIS locus products correlates with the capacity of the relevant MIS alleles to stimulate H-2compatible lymphocytes to proliferate. However, whether or not proliferation is in fact necessary for the development of suppression remains to be determined.…”
Section: Discussionsupporting
confidence: 85%
“…This conclusion corre-lates with observations suggesting that products of the Mls" locus have a regulatory role in the recognition of other DBA/2 antigens in vitro [20]. As suggested by several experiments [21,221, the suppressive effect of MIS locus products correlates with the capacity of the relevant MIS alleles to stimulate H-2compatible lymphocytes to proliferate. However, whether or not proliferation is in fact necessary for the development of suppression remains to be determined.…”
Section: Discussionsupporting
confidence: 85%
“…Oral administration may operate in a similar manner by deleting the reactive cells. 52 In conclusion, using the murine cGVHD model, we have shown that oral tolerization of donor toward recipient splenocyte proteins down-regulated the immune attack by donor effector cells on host target tissue. This led to amelioration of cGVHD of the skin, liver, and small intestines after splenocyte transplantation.…”
Section: Discussionmentioning
confidence: 72%
“…The increased survival is mediated by alloimmunization-activated suppressor cells which can decrease the intensity of the immune reaction developed by normal BIO.02 cells both in vivo (GVHR) and in vitro (proliferative response measured in mixed lymphocyte culture -MLC). H-2 GVHR were also suppressed by Mis preimmunization (Halle-Pannenko & Festenstein 1981). Genetic experiments with the congenic strain BALB.D2.Mls' were then designed to test whether the specific antigenic requirement for inducing suppression is indeed the Mis' haplotype.…”
Section: H-2 G Vh Suppressor (In Vivo) Effects Produced By Mis' Congementioning
confidence: 99%